Air quality and health effects of a transition to ammonia-fueled shipping in Singapore - Sagar Rathod; Morgan R Edwards; Chaitri Roy; Laura Warnecke; Peter Rafaj; Gregor Kiesewetter; Zbigniew Klimont (IOP Publishing, 2023)
Ammonia has been proposed to replace heavy fuel oil (HFO) in the shipping industry by 2050. When produced with low-carbon electricity, ammonia can reduce greenhouse gas emissions. However, ammonia emissions also contribute to local air pollution via the formation of secondary particulate matter. We estimate the potential ammonia emissions from storage and bunkering operations for shipping in Singapore, a port that accounts for 20% of global bunker fuel sales, and their impacts on air quality and health. Fuel storage and bunkering can increase total gaseous ammonia emissions in Singapore by up to a factor of four and contribute to a 25%-50% increase in ambient PM _2.5 concentration compared to a baseline scenario with HFO, leading to an estimated 210-460 premature mortalities in Singapore (30%-70% higher than the baseline). Proper abatement on storage and bunkering can reduce these emissions and even improve ambient PM _2.5 concentrations compared to the baseline. Overall, while an energy transition from HFO to ammonia in the shipping industry could reduce global greenhouse gas and air pollutant burdens, local policies will be important to avoid negative impacts on the communities living near its supply chain.